PENGARUH DIGITAL VISUAL MERCHANDISING DAN GREEN CONSUMER KNOWLEDGE TERHADAP KEPUTUSAN PEMBELIAN ONLINE THRIFTING DENGAN ENVIRONMENTAL SELF-IDENTITY SEBAGAI VARIABEL MEDIASI PADA GENERASI Z DI DAERAH ISTIMEWA YOGYAKARTA - Tiara Kusumastati; Ratri Nurina Widyanti (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM, 2026)
This study examines the influence of digital visual merch andising & green consumer knowledge on online thrifting purcha se decisions, with environmental self-identity as a mediating variable among Generation Z. A quantitative survey was conduct ed involving 100 responde nts selected through purposive sampl ing. Data were collected using a structured questionnaire and analyzed using PLS-SEM with SmartPLS 4. The findings reveal that digital visual merchand ising, green consumer knowledge, and environmental self-identity positively and significantly affect purchase decisions. Digital visual merchandising & green consum er knowledge significantly enhance environmental self-identity. Environmental self-identity does not mediate the effects of digital visual merchan dising or green consumer Knowledge on purchase decisions. Findings the importance of attractive digital product presentation & consumers' environment tal knowledge in encour aging online thrifting purchase decisions among Generation Z.